2015
DOI: 10.1016/j.jnnfm.2015.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Viscoplastic modeling of granular column collapse with pressure-dependent rheology

Abstract: International audienceA mechanical and numerical model of dry granular flows is proposed that quantitatively reproduce laboratory experiments of granular column collapse over inclined planes. The rheological parameters are directly derived from the experiments.The so-called \mu(I) rheology is reformulated in the framework of Drucker-Prager plasticity with the yield stress and viscosity \eta(||D||,p) depending on both the pressure p and the norm of the strain rate tensor ||D||. The granular domain, velocities, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

19
215
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(245 citation statements)
references
References 51 publications
19
215
1
Order By: Relevance
“…Furthermore, this continuum approach is in good agreement with discrete element simulations of granular column collapse [37]. Reference [32] showed that using a constant viscosity gives very similar results to using the µ(I) rheology for granular column collapses of small aspect ratios over horizontal and inclined planes. In all these regimes, the basic ingredients, required to reproduce dry granular flows at the "large scale" from the destabilization phase to the arrest phase, seem to be present in the proposed viscoplastic rheologies.…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…Furthermore, this continuum approach is in good agreement with discrete element simulations of granular column collapse [37]. Reference [32] showed that using a constant viscosity gives very similar results to using the µ(I) rheology for granular column collapses of small aspect ratios over horizontal and inclined planes. In all these regimes, the basic ingredients, required to reproduce dry granular flows at the "large scale" from the destabilization phase to the arrest phase, seem to be present in the proposed viscoplastic rheologies.…”
Section: Introductionsupporting
confidence: 61%
“…The so-called µ(I) rheology, where I is the inertial number, involves a viscosity that depends on the pressure and the strain rate experienced by the granular material. It enables to quantitatively reproduce granular column collapse over horizontal and inclined slopes and granular flow experiments over erodible substrate [35,32]. Furthermore, this continuum approach is in good agreement with discrete element simulations of granular column collapse [37].…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…More generally, this approach has been successfully applied in different geometries [2,3], e.g. silo discharge [11], granular chute flows [12][13][14][15] and granular column collapse [16,17], as well as to describe dynamic compressibility effects associated with spontaneous oscillatory motion [18,19]. Interestingly, experiments and numerical simulations have recently provided evidence for limie-mail: somfai.ellak@wigner.mta.hu tations of the μ(I)-rheology, when some non-local effects come into play (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…with various boundary values [7], mechanics [7] [8] [9], medical imaging and computational biology [10], geophysics [11], ontology regarding big data representation and storage [12], and elastica theory [13], to name just a few.…”
Section: Introductionmentioning
confidence: 99%